The Problems of Teaching Science in the Pages of the Magazine «Soviet Pedagogy» (1937–1991) - Nataliya Pobirchenko (Pedagogical Discourse, 2013)
The article analyzes the publications of pedagogical issues in the magazine «Soviet pedagogy» – a monthly scientific and theoretical journal of the Academy of Pedagogical Sciences of the USSR (Moscow, 1937–1991). The pages in the years covered topical issues of pedagogy – its methodology, education, training and education, development of domestic and foreign public education. The author singles out the main directions of publications of pedagogical issues in the magazine «Soviet pedagogy»: state policy in the field of education, theory and practice of pedagogy, the development of domestic and foreign schools and education, formation and development of domestic and foreign educational thought; actual problems of educational theory and practice.